Exploring antecedents of attitudes and skepticism towards pharmaceutical advertising and inter-attitudinal and inter-skepticism consistency on three levels: an international study. Issue 5 (3rd September 2018) - Koinig, Isabell; Diehl, Sandra; Mueller, Barbara
Abstract: Given the increasing relevance of over-the-counter (OTC) drugs to individuals' health and well-being, this study explores whether selected health variables, as well as consumers' attitudes and skepticism towards advertising in general, influence their attitudes and skepticism towards pharmaceutical advertising. It extends previous research by building on the theory of inter-attitudinal consistency, examining how three different levels of attitudes and skepticism are interrelated. A field study was conducted on three continents (727 subjects; non-student sample). Results reveal that consumer attitudes and skepticism towards advertising in general, influence attitudes and skepticism towards pharmaceutical advertising in particular, which positively impact the attitudes and skepticism towards four different ad appeal types. The study extends the theory of inter-attitudinal consistency to inter-skepticism consistency. Results further indicate that attitudes and skepticism towards advertising in general can be considered as key antecedents, but that several additional health-related factors also influence consumers' attitudes and skepticism towards pharmaceutical advertising. Moreover, attitudes and skepticism towards advertising in general, towards pharmaceutical advertising, as well as towards specific pharmaceutical ads, are negatively related. Reasons explaining these results are addressed, as are study limitations and implications for future research.